p53 methylation-the Arg-ument is clear - Durant, Stephen T.; Cho, Er Chieh; La Thangue, Nicholas B. (Cell cycle (Georgetown, Tex.), 2009)
p53 activity is of critical importance in suppressing human cancer formation, highlighted by the fact that the majority of human tumours have defective or inactive p53. In normal cells, p53 is held at low levels in a latent form and, following DNA damage, is stabilized which usually results in apoptosis or cell cycle arrest. Most functions of p53 can be ascribed to its role as a sequence specific transcription factor, and an extensive repertoire of downstream responsive genes have been identified. p53 activity is influenced by post-translational modifications, including phosphorylation and lysine methylation. Most recently, arginine methylation mediated by PRMT5, has been identified as an additional and important p53 modification. DNA damage induced p53 arginine methylation impacts on the biochemical properties and functional outcome of the p53 response.